A Ribosome Without RNA - Bernhardt, Harold S.; Tate, Warren P. (Frontiers in Ecology and Evolution, 2015)
It was Francis Crick who first asked why the ribosome contains so much RNA, and discussed the implications of this for the direct flow of genetic information from DNA to protein. Remarkable advances in our understanding of the ribosome and protein synthesis, including the recent publication of two mammalian mitochondrial ribosome structures, have shed new light on this intriguing aspect of evolution in molecular biology. We examine here whether RNA is indispensable for coded protein synthesis, or whether an all-protein ‘ribosome’ (or ‘synthosome’) might be possible, with a protein enzyme catalyzing peptide synthesis, and release factor-like protein adaptors able to read a message composed of deoxyribonucleotides. We also compare the RNA world hypothesis with the alternative ‘proteins first’ hypothesis in terms of their different understandings of the evolution of the ribosome, and whether this might have been preceded by an ancestral form of nonribosomal peptide synthesis catalyzed by protein enzymes.